2014
DOI: 10.1055/s-0034-1377580
|View full text |Cite
|
Sign up to set email alerts
|

Conventional vs. waterjet-assisted endoscopic submucosal dissection in early gastric cancer: a randomized controlled trial

Abstract: Waterjet-assisted ESD and conventional ESD are comparably effective and safe techniques for the local treatment of EGC. The waterjet-assisted technique is a faster and simpler procedure and requires fewer accessory changes compared with conventional ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 10 publications
3
37
0
Order By: Relevance
“…However, from our point of view, the device could work just using one anchorage point, and therefore, the procedure would be easier to carry out. Regarding waterjet-assisted ESD using Hybrid Knife, our results are consistent with reports in the only comparative study between waterjet-assisted ESD and conventional ESD [9], which showed waterjet-assisted ESD was both a faster and safer approach than ESD (20 % faster and less need of coagulation forceps). Furthermore, our preliminary experience with MG-ESD even improves …”
Section: Discussionsupporting
confidence: 89%
“…However, from our point of view, the device could work just using one anchorage point, and therefore, the procedure would be easier to carry out. Regarding waterjet-assisted ESD using Hybrid Knife, our results are consistent with reports in the only comparative study between waterjet-assisted ESD and conventional ESD [9], which showed waterjet-assisted ESD was both a faster and safer approach than ESD (20 % faster and less need of coagulation forceps). Furthermore, our preliminary experience with MG-ESD even improves …”
Section: Discussionsupporting
confidence: 89%
“…HK is a novel electrosurgical instrument whose function is the fusion of a submucosal injection and electrocautery. A previous study demonstrated that ESD using an HK is a faster and simpler procedure and requires fewer accessory changes than conventional ESD [11]. Our cases showed that an HK is also effective in pleuroscopic biopsy when malignant/benign fibrothorax is encountered.…”
Section: Discussionmentioning
confidence: 55%
“…A few studies have demonstrated that HK can reduce the frequency of device exchange and the procedure time[19,20]. Zhou et al[19] compared the procedure time, efficacy, and safety of HK-assisted ESD with the conventional technique in patients with early gastric cancer (EGC) in a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al[19] compared the procedure time, efficacy, and safety of HK-assisted ESD with the conventional technique in patients with early gastric cancer (EGC) in a randomized controlled trial. They revealed that HK-assisted ESD was as effective and safe as conventional devices (the IT-2 knife, Dual Knife and Hook Knife)-assisted ESD for treating EGC, but the HK group was associated with a shorter procedure time and a lower frequency of device exchange compared with the conventional group[19]. Furthermore, Cai et al[20] also demonstrated that HK achieved shorter procedure time, fewer accessory exchanges, less frequent use of coagulation forceps to control bleeding, and a lower bleeding rate in comparison with a triangle knife.…”
Section: Discussionmentioning
confidence: 99%